Successional pathways of Mediterranean evergreen vegetation on Sicily (Plant Ecology, 1988)
The Mediterranean evergreen vegetation of Sicily, comprised in the belt of the Quercetea ilicis, occupies a large part of the island. Human intervention (cutting, fire, pasture) has brought about a degradation of the natural vegetation. This study is based on our phytosociological research of the Quercetea ilicis belt on Sicily. With the 'habitat comparison' method, the dynamical relations between the different vegetation units have been defined. We distinguish the following stages, with reference to their vegetation structure: - a herbaceous stage formed by steppic vegetation, preceded by various types of nitrophilous-ruderal vegeta- tion on abandoned fields; - a garrigue stage dominated by half-shrubs; - a macquis stage with various distinct plant communities, four communities being important in regressive successions, and three in progressive ones; - a woodland and shrub-woodland stage with three different substages: pre-existent forests, present wood- lands, and woodlands which tend towards the final, stable stage of vegetation (potential natural vegetation). The dynamic relationships both in progressive and regressive successions have been synthesized in a scheme. In this scheme we have shown the main stages of the vegetation in their dynamics and we have constructed different series of vegetation types in two altitudinal belts, which are determined by varying environmental conditions of today. The results also show that in some cases the progressive series follow different pathways than the regressive series, and the final stage of the progressive series is different from the original vegetation.